The type of suture material affects transverse aortic constriction-induced heart failure development in mice: a repeated measures correlation analysis - Hackl, Benjamin; Zabrodska, Eva; Gewessler, Stefanie; Lilliu, Elena; Putz, Eva Maria; Kiss, Attila; Podesser, Bruno; Todt, Hannes; Ristl, Robin; Hilber, Karlheinz; Koenig, Xaver (Frontiers in Cardiovascular Medicine, 2023)
Introduction Transverse-aortic constriction (TAC) operation is a widely used animal model to induce hypertrophy and heart failure through left-ventricular pressure overload. In mice, the cardiac response to TAC exhibits considerable variability influenced by factors such as strain, sub-strain, age, sex and vendor. Methods To investigate the impact of suture material (silk versus prolene) and size (6-0 versus 7-0) on the TAC-induced phenotype, we performed surgeries on male C57BL6/N mice at 9 weeks of age defining the aortic constriction by a 27G needle, thereby employing most frequently used methodological settings. The mice were randomly assigned into four separate groups, 6-0 silk, 7-0 silk, 6-0 prolene and 7-0 prolene (10 mice per group). Echocardiography was conducted before TAC and every 4 weeks thereafter to monitor the development of heart failure. Repeated measures correlation analysis was employed to compare disease progression among the different groups. Results Our findings reveal a significant influence of the chosen suture material on TAC outcomes. Mice operated with prolene showed increased mortality, slower body weight gain, faster left-ventricular mass increase, and a faster decline in left-ventricular ejection fraction, fractional shortening and aortic pressure gradient compared to silk-operated mice. Moreover, despite non significant, using thinner suture threads (7-0) tended to result in a more severe phenotype compared to thicker threads (6-0) across all tested parameters. Discussion Collectively, our results highlight the importance of suture material selection in determining the cardiac phenotype induced by TAC and emphasize the need to consider this factor when comparing data across different research laboratories.